The gripping hand - Niven, Larry (Pocket Books, 1993)
The mysterious aliens known as Moties are divided into distinct biological forms: master, mediator, engineer, warrior. Each is adapted to its task, yet doomed by millions of years of evolution to an inescapable fate.